How to approach humans?: strategies for social robots to initiate interaction - Satake, Satoru; Kanda, Takayuki; Glas, Dylan F.; Imai, Michita; Ishiguro, Hiroshi; Hagita, Norihiro (2009 4th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2009)
This paper proposes a model of approach behavior with which a robot can initiate conversation with people who are walking. We developed the model by learning from the failures in a simplistic approach behavior used in a real shopping mall. Sometimes people were unaware of the robot's presence, even when it spoke to them. Sometimes, people were not sure whether the robot was really trying to start a conversation, and they did not start talking with it even though they displayed interest. To prevent such failures, our model includes the following functions: predicting the walking behavior of people, choosing a target person, planning its approaching path, and nonverbally indicating its intention to initiate a conversation. The approach model was implemented and used in a real shopping mall. The field trial demonstrated that our model significantly improves the robot's performance in initiating conversations.